Mechanical stretch and prostaglandin E2 modulate critical signaling pathways in mouse podocytes - Faour, Wissam (2010)
Elevated glomerular capillary pressure (Pgc) and hyperglycemia contribute to glomerular filtration barrier injury observed in diabetic nephropathy (DN). Previous studies showed that hypertensive conditions alone or in combination with a diabetic milieu impact podocyte cellular function which results in podocyte death, detachment or hypertrophy. The present study was aimed at uncovering the initial signaling profile activated by Pgc (mimicked by in vitro mechanical stretch), hyperglycemia (high glucose (HG), 25 mM d-glucose) and prostaglandin E2 (PGE2) in conditionally-immortalized mouse podocytes. PGE2 significantly reduced the active form of AKT by selectively blunting its phosphorylation on S473, but not on T308. AKT inhibition by PGE2 was reversed following either siRNA-mediated EP4 knockdown, PKA inhibition (H89), or phosphatase inhibition (orthovanadate). Podocytes treated for 20 min with H2O2 (10−4 M), which mimics reactive oxygen species generation by cells challenged by hyperglycemic or enhanced Pgc conditions, significantly increased the levels of active p38 MAPK, AKT, JNK and ERK1/2. Interestingly, stretch and PGE2 each significantly reduced H2O2-mediated AKT phosphorylation and was reversed by pretreatment with orthovanadate while stretch alone reduced GSK-3β inhibitory phosphorylation at ser-9. Finally, mechanical stretch alone or in combination with HG, induced ERK1/2 and JNK activation, via the EGF receptor since AG1478, a specific EGF receptor kinase inhibitor, blocked this activation. These results show that cellular signaling in podocytes is significantly altered under diabetic conditions (i.e., hyperglycemia and increased Pgc). These changes in MAPKs and AKT activities might impact cellular integrity required for a functional glomerular filtration barrier thereby contributing to the onset of proteinuria in DN.